(untitled) (Ameghiniana, 2018)
Titanosauria is a clade of sauropod dinosaurs which includes the largest terrestrial animals of all times and an outstanding feature of some species of this group is the presence of osteoderms. In Brazil, these elements are rare and only six were identified up to date. Here, we describe the first titanosaur osteoderm from the Potiguar Basin. The osteoderm is held in coleção de Vertebrados Fósseis of Universidade Federal do Rio de Janeiro by the number UFRJ DG 549-R. The specimen presents a bilateral symmetry and is assigned to the bulbous ellipsoid morphotype, with the internal face flattened and dome-like external face, forming a prominent bulb. Structurally, the osteoderm presents a large trabecular area filling most the inner cavity, with compact bone only in the outer region. Based on the last functions hypothesis, this individual has used the osteoderms as a source of calcium, possibly, during oogenesis, but a taphonomical cause cannot be ruled out. The Potiguar osteoderm shows more similarities with the osteoderm of Ibirá (Bauru Group, Turonian-Santonian), despite the greater geographical and temporal proximity to the material of the São Luís Basin (Middle Cretaceous). This may indicate a more diverse armored titanosaur fauna (Lithostrotia) on the Northeastern region of Brazil at Cretaceous period.